Effects of OTT services on consumer's willingness to pay for optical fiber broadband connection in Thailand - Tatcha Sudtasan; Hitoshi Mitomo (International Telecommunications Society (ITS), 2016)
Over-the-top (OTT) media and communications services are shifting internet consumption towards the increase of traffic over the internet. Since FTTH provides the highest capacity and speed of the broadband service, this paper attempts to examine the impact of OTT services to consumers to subscribe FTTH as an efficient off-load option from mobile broadband. Main research questions are whether and how OTT services affect and drive consumers to adopt optical fiber broadband. It uses fuzzy data to derive consumer's willingness to pay (WTP) for optical fiber broadband connection. The results of the study indicate that movie over internet service as an OTT service drives people to adopt and be willing to pay more for FTTH connection. The paper also discusses the policy implication on the promotion of optical fiber broadband adoption in Thailand.
Keywords: 330; Optical fiber; Willingness to pay; OTT services; Fuzzy data